Mental Health Patterns and Consequences : Results from Survey Data in Five Developing Countries - Das, Jishnu; Do, Quy-Toan; Friedman, Jed; McKenzie, David (World Bank, 2012)
The social and economic consequences of poor mental health in the developing world are presumed to be significant, yet remain underresearched. This study uses data from nationally representative surveys in Bosnia and Herzegovina, Indonesia, and Mexico and from special surveys in India and Tonga to show similar patterns of association between mental health and socioeconomic characteristics. Individuals who are older, female, widowed, and report poor physical health are more likely to report worse mental health. Individuals living with others with poor mental health are also significantly more likely to report worse mental health themselves. In contrast, there is little observed relation between mental health and consumption poverty or education, two common measures of socioeconomic status. Indeed, the results here suggest instead that economic and multidimensional shocks, such as illness or crisis, can have a greater impact on mental health than poverty. This may have important implications for social protection policy. Also significant, the associations between poor mental health and lower labor force participation (especially for women) and more frequent visits to health centers suggest that poor mental health can have economic consequences for households and the health system. Mental health modules could usefully be added to multipurpose household surveys in developing countries. Finally, measures of mental health appear distinct from general subjective measures of welfare such as happiness.